Differential regulation of accumbal dopamine transmission in rats following cocaine, heroin and speedball self-administration - Pattison, Lindsey P. (2012)
Cocaine/heroin combinations (speedball) exert synergistic neurochemical and behavioral effects that are thought to contribute to the increased abuse potential and subjective effects reported by polydrug users. In vivo fast-scan cyclic voltammetry (FSCV) was used to examine the effects of chronic intravenous self-administration (25 consecutive sessions) of cocaine (250 μg/inf), heroin (4.95 μg/inf) and speedball (250/4.95 μg/inf cocaine/heroin) on changes in electrically evoked dopamine (DA) efflux, maximal rate of DA uptake (V(max)) and the apparent affinity (K(m)) of the dopamine transporter (DAT) in the nucleus accumbens (NAc). The increase in electrically evoked DA was comparable following cocaine and speedball injection; however, heroin did not increase evoked DA. DAT K(m) values were similarly elevated following cocaine and speedball, but unaffected by heroin. However, speedball self-administration significantly increased baseline V(max), while heroin and cocaine did not change baseline V(max), compared to the baseline V(max) values of drug-naïve animals. Overall, elevated DA clearance is a likely consequence of synergistic elevations of NAc extracellular DA concentrations by chronic speedball self-administration, as reported previously in microdialysis studies. The present results indicate neuroadaptive processes that are unique to cocaine/heroin combinations and cannot be readily explained by simple additivity of changes observed with cocaine and heroin alone.